Estrutura e Evolução dos Cordões Arenosos Pleistocênicos no Canal de Acesso à Laguna dos Patos-RS, Brasil - CORRÊA, IRAN CARLOS STALLIVIERE; ALIOTTA, SALVADOR; WESCHENFELDER, JAIR (Pesquisas em Geociências, 2004)
<!– .p text-align: justify; –> This work presents the results of a high-resolution seismic reflection data survey carried out in the Patos lagoon inlet, near Rio Grande the southernmost harbor of Brazil. The analysis of the reflection patterns reveals the presence of transgressive/regressive barrier structures and beach/foredune-ridges. The mapping of these barrier structures allows a better understanding of the geological evolution of the Patos lagoon system during the Quaternary period and also helps to understand the evolution and migration of the actual lagoonal inlet between the Patos lagoon and Atlantic Ocean.